Russia - Republic of Korea: results and prospects (30 years of diplomatic relations) - O. G. Karpovich; L. A. Smagina (Сравнительная политика, 2021)
The Republic of Korea is one of Russia's priority partners in the Asia-Pacific region. In 2020, the countries celebrate the 30th anniversary of the establishment of diplomatic relations. In recent years, the countries have made significant steps towards strengthening trade and economic cooperation. In February 2019, the countries signed an action plan for implementing 9 priority areas of cooperation - natural gas, energy, Railways, seaports, the Northern sea route (NSR), shipbuilding, industrial complexes, agriculture and fishing. The Russian-Korean innovation center was opened, and in September 2020 an agreement of intent was signed to create a South Korean industrial Park in Primorsky kray. At the end of 2019, Moscow and Seoul decided to declare 2020 “The year of mutual exchanges”.